Solutions with peculiarities of one equation of mathematical physics - Gutlyansky , V. Ya.; Ryazanov , V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A theorem for the representation of solutions with singularities of logarithmic type of a certain equation of mathematial physics in terms of quasiconformal mappings is obtained.